THE ROLE OF SOCIO-EMOTIONAL PARENTING ON CHILDREN’S STUDYING MOTIVATION AND INTEREST DURING THE COVID-19 PANDEMIC IN SAMBAS, WEST KALIMANTAN - Lessy, Zulkipli; Barokah, Mabid; Rohman, Miftahur (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2021)
This study examines the influence of socio-emotional parenting towards children's motivation for, and interest in, studying. More particularly, the parental influences were observed while the children studied at home during the Covid-19 pandemic. The sample (n = 66) was drawn from the population of students in the sub-district of Sambas, in the West Kalimantan region of Indonesia. Data was examined to assess parental influences on improvement in children's motivation and interest. This quantitative research applied simple regression analysis to the data. The analysis implementation uses the classical assumption test and hypothesis test with the assistance of SPSS for Windows version 26. The research results show that (1) there was a significant influence of 7.3% of the socio-emotional parenting role towards children's motivation to study at home during the Covid-19 pandemic; (2) there was a significant influence of 18.4% in the role of socio-emotional parenting towards a child's interest in studying at home during the Covid-19 pandemic; and (3) there was a significant influence of as much as 64% on a child's interest in studying at home during the Covid-19 pandemic.